A molecular switch for selective autophagosome formation - Kamber, Roarke A (Autophagy, 2015)
Selective macroautophagy (hereafter autophagy) can eliminate large cytotoxic structures that are designated for degradation by autophagy receptors. In our recent paper, we showed that a key function of target-bound autophagy receptors is to activate the autophagy kinase, Atg1, via interactions with the scaffold protein Atg11. Our work thus reveals a mechanism by which target recognition coordinates the earliest steps in autophagosome biogenesis.